Microbial Metabolite Inspired β‐Peptide Polymers Displaying Potent and Selective Antifungal Activity. Issue 14 (20th March 2022) - Zhang, Donghui; Shi, Chao; Cong, Zihao; Chen, Qi; Bi, Yufang; Zhang, Junyu; Ma, Kaiqian; Liu, Shiqi; Gu, Jiawei; Chen, Minzhang; Lu, Ziyi; Zhang, Haodong; et al.
Abstract: Potent and selective antifungal agents are urgently needed due to the quick increase of serious invasive fungal infections and the limited antifungal drugs available. Microbial metabolites have been a rich source of antimicrobial agents and have inspired the authors to design and obtain potent and selective antifungal agents, poly(DL‐diaminopropionic acid) (PDAP) from the ring‐opening polymerization of β ‐amino acid N ‐thiocarboxyanhydrides, by mimicking ε ‐poly‐lysine. PDAP kills fungal cells by penetrating the fungal cytoplasm, generating reactive oxygen, and inducing fungal apoptosis. The optimal PDAP displays potent antifungal activity with minimum inhibitory concentration as low as 0.4 µg mL −1 against Candida albicans, negligible hemolysis and cytotoxicity, and no susceptibility to antifungal resistance. In addition, PDAP effectively inhibits the formation of fungal biofilms and eradicates the mature biofilms. In vivo studies show that PDAP is safe and effective in treating fungal keratitis, which suggests PDAPs as promising new antifungal agents. Abstract : Inspired by ε ‐poly‐lysine produced from the fermentation of Streptomyces albulus, the β ‐peptide polymer poly(DL‐diaminopropionic acid) (PDAP) bearing much higher charge density than ε ‐poly‐lysine, is designed. PDAP is synthesized via the moisture tolerant polymerization of β ‐amino acid N ‐thiocarboxyanhydrides. Compared to ε ‐poly‐lysine that has weak antifungal activity, PDAP displays potent and selective antifungal activity and strong therapeutical potential.